The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/antibiotics11121681
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Clinically Available Beta-Lactamase Inhibitors Combined with Cefiderocol against Carbapenemase-Producing Gram-Negative Organisms

Abstract: The role of β-lactamases in reduced susceptibility or resistance to cefiderocol has been supported by recent reports. The purpose of this study was to investigate the in vitro impact of clinically available β-lactamase inhibitors on cefiderocol activity against characterized carbapenemase-producing Gram-negative isolates. A collection of 39 well-characterized Gram-negative isolates obtained from various clinical sources and countries were included. Cefiderocol antimicrobial susceptibility was evaluated via ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…In line with the current metaanalysis, a prior systematic review on mechanisms of CFDC-NS by the same authors, identified several β-lactamases (and various other mechanisms) that may result in higher MIC of cefiderocol, notably NDM and KPC variants conferring resistance for CZA [6]. Of interest, combination of cefiderocol with β-lactamases may be able to overcome resistance [6,110].…”
Section: Discussionsupporting
confidence: 57%
“…In line with the current metaanalysis, a prior systematic review on mechanisms of CFDC-NS by the same authors, identified several β-lactamases (and various other mechanisms) that may result in higher MIC of cefiderocol, notably NDM and KPC variants conferring resistance for CZA [6]. Of interest, combination of cefiderocol with β-lactamases may be able to overcome resistance [6,110].…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, disk diffusion can also be affected by remarkable variability depending on the various combinations of disks and agar media manufacturers [34,37]. Additional commercial systems for cefiderocol susceptibility testing have recently been developed, and evaluations of the available systems are underway with variable results [39][40][41][42][43].…”
Section: Cefiderocol Susceptibility Testing Issuesmentioning
confidence: 99%
“…The plant extract exhibiting highest synergistic activities was subjected to the time-kill assay to further analyze its β-Lactam amplifying potentials (López-Malo et al, 2020;Bianco et al, 2022). For this purpose, 200µl of MH broth, 20µl of meropenem, 10µl of Green tea extract and 20µl of freshly prepared bacterial culture in nutrient broth were added to the wells of microtiter plate.…”
Section: Time-kill Assaymentioning
confidence: 99%